Breaking barriers a study on the implementation, sustainability and user/community perception of a "free library" based on the Reading Club 2000 in Barangay La Paz, Makati City - Imperial, Chris Martin T. (2013)
Since its inception in the year 2000, the Reading Club 2000 in Brgy. La Paz, Makati City has gained popularity among local and international media because of its "free library" system. The library has a revolutionary system that allowed its users to access the collection for free. Its books were given away for free in a library that never closes. The system exuded a huge potential to augment the coverage of public libraries in the Philippines. It is in this light that this study has coined the term, investigated library's sustainability and focused on the Reading Club 2000 being a template for all similar libraries that would follow.